ANALYSIS ON CALCIUM SOLUBILITY IN KIDNEY STONES (IN VITRO) AND DIURETIC EFFECT (IN VIVO) USING CORN SILK (ZEA MAYS L.) INFUSE - Pardede, Tuty Roida; Muchlisyam, Muchlisyam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Investigation has been carried out about infuse of corn silk (Zea mays L.) concerning the solubility of kidney stone in vitro and the diuretic effect in vivo. Methods: The methodology of research conducted in the form of dissolving kidney stones in corn silk infuse with a concentration of 2%, 4%, 6%, 8%, and 10%, then incubated at 37Â°C for 4 h. The solubility of calcium is known by measuring the levels of early calcium and after incubated with kidney stones. Potassium (K) is a substance that can dissolve kidney stones in infuse and also measured by atomic absorption spectrophotometry. The diuretic effect study used male rats which were divided into 7 groups that consisted of 1 positive control (treated with furosemide), 1 negative control treated with CMC Na 0.5 % and 5 groups treated with infuse of corn silk in 5 different concentration (2%, 4%, 6%, 8%, and 10%). Results: Increase in calcium levels after incubation with kidney stone using corn silk infuse with various concentrations. The levels of Ca dissolved in the infuse of 2%, 4%, 6%, 8%, and 10%, respectively, were 2.2600 Î¼g/ml, 5.5733 Î¼g/ml, 7.9267 Î¼g/ml, 10.9233 Î¼g/ml, and 8.7667 Î¼g/ml. It was found that the urine volume for 24 h was significant with 2%, 8%, and 10% corn silk infuse. Conclusion: Infuse of corn silk could decrease kidney stones, and it was diuretic. This research supported the aim of traditional corn silk decoction for the same intention.